Toward an “Ancient” Virtual World: Improvement Methods on X-ray CT Data Processing and Virtual Reconstruction of Fossil Skulls - Pérez-Ramos, Alejandro; Figueirido, Borja (Frontiers in Earth Science, 2020)
This article focuses on virtual advances to solve technical problems usually encountered by paleontologists, such as (i) the limited acquisition size of the computed tomography machines to acquire data on large structures, (ii) the use in the same study of biological objects acquired with different types of computed tomography, and therefore different resolutions, and (iii) matrix removal within the fossil (cranial cavities, intra-trabecular cavities, among others cavities). All these problems are very common problems in paleontology, and therefore, solving then is important to save effort and the time invested in data processing. We propose various solutions to remove such artefacts, based on new technical advance focused on improving and processing the images obtained from the X-ray computed tomography acquisition. Other aspects could be the use of filters to remove background noise from XCT data and measuring histograms to remove artefacts. Such artefacts are the result of recrystallizations or very dense materials within the samples, especially fossils due to the taphonomic fossilization process or derived from anthropogenic restoration of fossils. Accordingly, here, we provide a protocol to gradually acquire data on samples with size that exceed the size of the acquisition window of the X-ray tomography machine, joining the parts with enough accuracy and resolution, and we propose the use of the interpolation "bicubic" method. Moreover, using this method it is possible to use medical XCT data together with Xmicro-CT data, which opens new ways to use different tools to be able to rotate or move the acquired data within the image stack. Another advantage is the use of plugins for quantitative analysis, which is necessary to have data with isometric voxels, such as the BoneJ plugin of the software ImageJ. We also deal with the problem of eliminating the exogenous material that usually fills the internal cavities of fossils by means of using filters based on edge detection by gradient. Applying this method, it is possible to segment the non-bony matrix parts more quickly and efficiently. All of this is exemplified using five fossil skulls belonging to the cave bear group, an iconic fossil species from the Pleistocene of Eurasia.